DEVELOPMENT OF VIRTUAL STENTING METHODS OF FLOW DIVERTER STENTS USING SPRING-DAMPER ANALOGY FOR A COMPUTATIONAL FLUID DYNAMICS-BASED THERAPY EVALUATION OF AN INTRACRANIAL ANEURYSM CASE - Nainggolan, Bonfilio
Stroke is one of the leading causes of death in Indonesia and is ranked as the third most economically taxing disease for the national healthcare system in 2014-2018. One of the main causes of stroke is the rupture of intracranial aneurysms which are bulgings of blood vessels located in the brain. The use of flow diverter (FD) stents is one of the treatment options where blood flow to the aneurysm is diverted back into the parent vessel without having to directly block the aneurysm, thus allowing the aneurysm to heal naturally. FDs are commonly imported which contributes to the economic burden of the healthcare system. Therefore, there is motivation to start producing FDs domestically. To be able to independently produce FDs, a method to evaluate the efficacy of FD designs before having clinical trials is needed. To this end, computational simulations that can predict the effects of FD treatments hold an essential role as the starting point of the national FD research and development. In this work, a fast virtual stenting algorithm which employ a spring expansion model is implemented along with a method to evaluate the performance of deployed FDs based on Computational Fluid Dynamics (CFD) simulations, both of which are fully based on open-source softwares. It is shown that the implemented virtual stenting method can accommodate the deployment of various FD designs on a multitude of idealized and realistic vessel models within one minute of comuption time. The effects of FD deployment were then studied on a real aneurysm geometry based on the implemented aneurysm stability evaluation method. The CFD simulations done on the case show that the FD deployment reduces wall shear stress (WSS) by 82% (from 1,64 Pa to 0,29 Pa), reduces mass inflow rate to the aneurysm (IR) by 8%, and reduces energy loss rate due to the aneurysm (EL) by 15%. These results demonstrates that the deployment of an FD in this case tend to reduce the parameters associated with aneurysm rupture, albeit not to the extent needed to fully stabilize the aneurysm.